2004
DOI: 10.1143/jjap.43.7467
|View full text |Cite
|
Sign up to set email alerts
|

Field-Induced Strain of Shape Memory Alloy Fe–31.2%Pd Using a Capacitance Method in a Pulsed Magnetic Field

Abstract: The theory of the premelting phenomena in ionic crystals has been developed on the basis of the concept of heterophase fluctuation in the vicinity of their melting points. The size of the liquid-like clusters is estimated by the theory using the experimental specific heat value. Molecular dynamics simulations are also performed in NaCl and AgBr crystals to examine the ionic configuration in the premelting region. The structural features are discussed using the Lindemann instability criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…As seen in the figure, a large strain of about 1% with a small hysteresis is obtained at 20 K. This strain is nearly five times as large as the magnetostriction of Terfenol-D. To make use of FMSMAs as actuator materials, a quick response of strain to the magnetic field is desirable. Recently, it has been confirmed by Sakon et al, using Fe-31?2Pd 14 and Fe 3 Pt 15 , that almost the same results of MFIS shown in Fig. 5 can be induced by a pulsed magnetic field with a pulse duration of 5 ms.…”
Section: Martensitic Transformation In Fe-31?2pd Fe3pt and Ni2mngasupporting
confidence: 56%
“…As seen in the figure, a large strain of about 1% with a small hysteresis is obtained at 20 K. This strain is nearly five times as large as the magnetostriction of Terfenol-D. To make use of FMSMAs as actuator materials, a quick response of strain to the magnetic field is desirable. Recently, it has been confirmed by Sakon et al, using Fe-31?2Pd 14 and Fe 3 Pt 15 , that almost the same results of MFIS shown in Fig. 5 can be induced by a pulsed magnetic field with a pulse duration of 5 ms.…”
Section: Martensitic Transformation In Fe-31?2pd Fe3pt and Ni2mngasupporting
confidence: 56%
“…On the other hand, the MFISs without a bias stress have been observed in the Fe-Pd and Fe-Pt alloys. As for a Fe-31.2%Pd (at.%) single crystal alloy, a strain of 0.4% has been observed in single-shot pulse fields at the fields of 12 kOe with a frequency of 80 Hz at 77 K, which is much lower than the martensite transformation temperature T M = 230 K [58]. With regard to the Fe 3 Pt single crystal alloy, an MFIS of 1.7% has been observed and a recoverable strain of about 0.6% has been induced in single-shot pulse fields at the fields of 20 kOe with a frequency of 160 Hz at 4.2 K in the martensite state (T M = 85 K) [59].…”
Section: Magnetic Field-induced Strain and Magnetostriction In Shape mentioning
confidence: 91%
“…Then, the direction of the sample was turned over, and a magnetic field was applied. Precise explanations of the magnetization measurement are reported in [17].…”
Section: Magnetization Of the Neomax Permanent Magnetmentioning
confidence: 99%